Linearized teixobactin is inactive and after sequence enhancement, kills methicillin‐resistant Staphylococcus aureus via a different mechanism. Issue 5 (25th April 2022) - Wu, Qianhui; Mishra, Biswajit; Wang, Guangshun
Abstract: Staphylococcus aureus ( S. aureus ) is a highly adaptable pathogen that can rapidly develop resistance to conventional antibiotics such as penicillin. Recently, teixobactin was discovered from uncultivated soil bacteria by using the i‐chip technology. This depsipeptide forms an ester bond between the backbone C‐terminal isoleucine carboxylic acid and the hydroxyl group of threonine at position 8. Also, it contains multiple nonstandard amino acids, making it costly to synthesize. This study reports new peptides designed by linearizing teixobactin. After linearization and conversion to normal amino acids, teixobactin lost its antibacterial activity. Using this inactive template, a series of peptides were designed via hydrophobic patching and residue replacements. Three out of the five peptides were active. YZ105, only active against Gram‐positive bacteria, however, showed the highest cell selectivity index. Different from teixobactin, which inhibits cell wall synthesis, YZ105 targeted the membranes of methicillin‐resistant S. aureus (MRSA) based on kinetic killing, membrane permeation, depolarization, and scanning electron microscopy studies. Moreover, YZ105 could kill nafcillin‐resistant MRSA, Staphylococcal clinical strains, and disrupted preformed biofilms. Taken together, YZ105, with a simpler sequence, is a promising lead for developing novel anti‐MRSA agents. Abstract :